Seeking Truth in Changing Journalism: An Ambivalent Notion in Rede Globo - Gadret, Débora Lapa; Reginato, Gisele Dotto (Brazilian journalism research, 2016)
Truth has been a central notion for journalism as a social institution. In current times, when journalistic role and practices are being challenged by audiences and by media reconfigurations, it is important to ask how the field’s traditional values are being reorganized. Thus, the objective of this paper is to analyse how Brazilian television network Rede Globo comprehends the notion of truth in 2014’s institutional commercials. Through discourse analysis of their campaign, we found that the concept being presented is ambivalent: sometimes, truth is a unified entity and at other times it is multiple. Even though there is an ambiguity when presenting this value, journalism is always shown as responsible for mediating access to truth(s), high lightening journalistic relevance to society.